1971
DOI: 10.1111/j.1432-1033.1971.tb01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Coded by Mitochondrial DNA of Mammalian Cells

Abstract: Improved conditions are described for the maintenance of protein synthesis by isolated liver mitochondria. The products of synthesis in vitro are first attached to a 55-S mitoribosome (mitochondrial-ribosome) but move off the mitoribosome as completed peptide chains in less than 15 min a t 30 "C. Over a 1-h period of incubation there is no change in the spectrum of molecular weights of the peptides being synthesized. The protein synthesized by isolated hamsterliver mitochondria were compared with those synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1973
1973
1978
1978

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…Coote and Work [46] concluded to identical patterns of synthesis in vitro and in vivo in BHK-1 cells, both products being in the molecular weight range 23000-43000. Similar findings for rat liver are reported by Ibrahim et al [46]. Tzagoloff and Akai [47] studying the product in vivo in yeast found that its electrophoretic behaviour in dodecylsulfate polyacrylamide gels depended entirely on the method of preparation of the product.…”
Section: Molecular Weight Of Ribosome-bound Productssupporting
confidence: 76%
“…Coote and Work [46] concluded to identical patterns of synthesis in vitro and in vivo in BHK-1 cells, both products being in the molecular weight range 23000-43000. Similar findings for rat liver are reported by Ibrahim et al [46]. Tzagoloff and Akai [47] studying the product in vivo in yeast found that its electrophoretic behaviour in dodecylsulfate polyacrylamide gels depended entirely on the method of preparation of the product.…”
Section: Molecular Weight Of Ribosome-bound Productssupporting
confidence: 76%
“…They are also similar to the profiles of proteins labelled in isolated mitochondria from HeLa cells [31], BHK-21 cells [32] or rat liver [33]. In general, the proteins are often found as two or three poorly resolved classes having apparent molecular weights of less than 50000.…”
Section: Discussionsupporting
confidence: 49%
“…Somewhat lower rates of mitochondrial protein synthesis in the presence of various cytoplasmic inhibitors have been found by Perlman and Penman [20] and Brega and Baglioni [21] for HeLa cells incorporating labelled leucine. Any direct inhibitory effect of emetine or cycloheximide on mitochondrial protein synthesis [18,22] [23]) is probably too low since (a) the mitochondria analysed were not completely pure (see Table 1 and Fig. 6), and (b) cycloheximide might have some direct and/or indirect inhibitory effect on mitochondrial protein synthesis.…”
Section: Properties Oj Proteins Synthesized By Mitochondria In Intactmentioning
confidence: 99%